PENGETAHUAN GURU GEOGRAFI TENTANG SISTEM INFORMASI GEOGRAFI (SIG) DI SMAN KABUPATEN SIJUNJUNG - Roni - Firdaus; Yurni Suasti (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to describe the knowledge of geography teachers about Geographical Information Systems (GIS) at SMAN Sijunjung Regency based on gender, length of teaching, and ownership of certification. This type of research is descriptive using a survey method. The result of this research indicate that: 1). Geography teachers’ knowledge of GIS material at SMAN Kabupaten Sijunjung based on gender, shows a tendency know better than female teachers; 2). Geography teachers knowledge about GIS material at SMAN Kabupaten Sijunjung based on the legenth of teaching, shows a tendency that the knowledge of teachers who teach >20 years is better than teachers who teach <20 years; 3). Geography teachers knowledge of GIS material at SMAN Kabupaten Sijunjung based on ownership of certification, shows a tendency that the knowledge of teachers who have been certified is higher than teachers who are not yet certified.